ROLA ZWIĄZKÓW ZAWODOWYCH W PODNOSZENIU KWALIFIKACJI PRACOWNIKÓW - Surdykowska, Barbara (Zeszyty Prawnicze, 2016)
THE ROLE OF TRADE UNIONS IN THE ENHANCEMENT OF EMPLOYEES’ QUALIFICATIONS Summary The aim of this article is to discuss the enhancement of employees’ qualifications as an area for the potential joint involvement of Polish trade unions and employers’ organisations, and particularly for the assessment of the negotiability of solutions to remedy the current situation, which is giving rise to concern. The author attempts to answer the question whether the policy pursued by Polish trade unions entails a commitment to the idea that the enhancement of professional qualifications may serve as an efficient tool to secure jobs. The same question is also put with respect to employers, who do not appear to be very interested in negotiating such issues or even in general in Staff training, either. The attitude of diffidence may be explained by the fact that in comparison with the 15 member states of the pre-2004 EU, in Poland entrepreneurs receive a relatively low level of state support for continuing professional training for their staff. This observation applies not only to insufficient fiscal incentives but also to inadequate counselling services. In the author’s opinion collective bargaining on effective professional training and qualification enhancement programmes cannot be conducted without a profound transformation of the model for the allocation of financing from the Labour Fund. This should also entail raising the joint responsibility of employers and trade unions, which cannot be done unless an incentive in the form of tax relief on professional training courses comes from the legislator. Until such changes are introduced, the issue will continue to be perceived as it has been up to now – as a matter concerning an individual’s right to work, not as the collective interest of employees represented by their trade unions.